All Days 2015
DOI: 10.4043/25770-ms
|View full text |Cite
|
Sign up to set email alerts
|

Successful Real Time Instrumentation Of The Conductor And Surface Casing Of An Exploration Subsea Well In The North Sea To Measure The Actual Loads Experienced During Drilling Operations

Abstract: In recent years, proper documentation of adequate wellhead fatigue capacity for a planned drilling operation became progressively more important while simultaneously challenging to achieve with traditional wellhead design and existing fatigue analyses methodologies applied. These challenges have developed as a result of the increase in size of drilling rigs and Blowout Preventers (BOPs), longer drilling campaigns on wells, and operations in harsher environments. In response, the industry started directing its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Few studies evaluating the Zakeri et al (2015) model based on field data have already been reported in literature (Kannala et al 2016, Myhre et al 2015, Lindstad et al 2015. While the method proposed performs very well in predicting the wellhead fatigue damage from the model test, the reliability of the new method needs to be verified using field data collected during a drilling campaign.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies evaluating the Zakeri et al (2015) model based on field data have already been reported in literature (Kannala et al 2016, Myhre et al 2015, Lindstad et al 2015. While the method proposed performs very well in predicting the wellhead fatigue damage from the model test, the reliability of the new method needs to be verified using field data collected during a drilling campaign.…”
Section: Introductionmentioning
confidence: 99%